Zen-brain horizons : toward a living zen - Austin, James H., 1925- (Cambridge, Massachusetts : The MIT Press, 2014)
A neurologist and Zen practitioner clarifies the benefits of meditative training, drawing on classical Buddhist literature and modern brain research.
"In Zen-Brain Horizons, James Austin draws on his decades of experience as a neurologist and Zen practitioner to clarify the benefits of meditative training. Austin integrates classical Buddhist literature with modern brain research, exploring the horizons of a living, neural Zen. When viewed in the light of today, the timeless wisdom of some Zen masters seems almost to have anticipated recent research in the neurosciences. The keen attentiveness and awareness that we cultivate during meditative practices becomes the leading edge of our subsequent mental processing. Austin explains how our covert, involuntary functions can make crucial contributions to the subtle ways we learn, intuit, and engage in creative activities. Austin begins by looking back at ancient Buddhist narratives. He then weaves together the major themes of self, attention, emotion, language, and insight. He goes on to examine Zen and psychology as cultural developments, including recent information about how a clear, calm awareness can change the meditating brain. He considers the pathways through which intuitions develop on their way to becoming realized, exploring the phenomena of the spontaneous color imagery that arises during meditation. Looking out even further into the future, Austin discusses the universal themes of creativity, happiness, openness, and selflessness. Along the way, he bows in homage to William James, explores 'Buddhist Botany' and 'Avian Zen, ' demonstrates why living Zen means much more than sitting quietly indoors on a cushion, and provides simplified advice that helps guide readers to the most important points"--MIT CogNet.
By way of a personal introduction -- Looking far back into the distant past -- Two old men consult the Buddha -- Neuropsychological aspects of the attentive self -- Neural correlations of meditating selflessly -- Buddhist botany 101 -- Looking back into earlier centuries of the Common Era -- A glimpse of "just this" in Tang dynasty China (618-907) -- Avian Zen -- Homage to William James -- Sampling recent reports -- Recent clinical information -- Mindfulness starts as present-moment awareness -- Subconscious background qualities that can infuse awareness -- Looking out into the distance above the horizon -- Reprocessing emotionally traumatic imagery while elevating the gaze -- Spontaneous color imagery during meditation -- A way out of the grand delusion -- Peering into the future -- New research horizons -- Resources of enduring happiness; opening to "just this" -- In closing -- Appendix A. The forest as a sanctuary for re-creation -- Appendix B. Potentially useful words and phrases -- Appendix C. Common acronyms used in brain research -- Appendix D. Elephants in the living room.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 650
Keywords: Zen Buddhism; Brain -- Religious aspects -- Zen Buddhism; Cognitive neuroscience; RELIGION -- Comparative Religion; Brain -- Religious aspects; Cognitive neuroscience; Zen Buddhism; Electronic books